Early Recanalization of a Traumatic Coronary Artery Dissection With Medical Therapy Alone - Edward R. Rojas, MD; Lawrence W. Gimple, MD; Mohamed Morsy, MD; Todd C. Villines, MD (JACC: Case Reports, 2020)
We describe a patient who presents with chest discomfort 30 h after having an accident with an all-terrain vehicle. His follow-up coronary computed tomography angiogram revealed early recanalization of his coronary artery with conservative medical therapy. (Level of Difficulty: Intermediate.)